Satisfaction survey of patients hospitalized in the Department of Clinical Neurological Rehabilitation and systemic USK in Olsztyn - Szypulska, Anna; Fischer, Beata; Gutysz-Wojnicka, Aleksandra; Ozga, Dorota (Journal of Education, Health and Sport, 2017)
Introduction. As a result of rising patient expectations and the implementation of medical priority for medical facilities is an increase in satisfaction with the quality of services offered. Identify areas requiring modification is possible by analyzing patient satisfaction. Verification of the data makes it possible to request that the recipient have to say about the services offered at the institution, as well as help determine dysfunctions of the activities of these institutions. The aim of the study is to evaluate the satisfaction of patients hospitalized in the Department of Clinical Neurological Rehabilitation and systemic University Hospital in Olsztyn. Material and methods. The survey questionnaire survey was conducted based on the original questionnaire using Likert scale. Respondents were hospitalized at the University Clinical Hospital in Olsztyn. Statistical analyzes were performed using Statistica 10PL Results. Overall satisfaction with the received health benefits patients assessed at 4.1 on a scale of 1-5. In contrast, satisfaction with health services performed by nurses rated at 4.7, and the activities performed by a doctor and physiotherapists rated at 4.3.The lowest level of satisfaction applies to the first contact of the patient with the hospital staff (3.1).Conclusions. The level of patient satisfaction with medical procedures depends on patients educational level. Top rated benefits are realized by nurses. Patient’s expectations are varied in relation to the members of the therapeutic team. The first contact with the patient has no effect on the final assessment of the medical services. Overall satisfaction with the quality of medical services is satisfactory.